2011
DOI: 10.1080/03602559.2011.553861
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surfactants on the Properties of Styrene/Methacrylate–Type Superplasticizer in Cement Paste

Abstract: Copolymer emulsion lattices based on styrene (St) with methacrylate monomers, were synthesized with composition ratio (5/5) in the presence of a co-surfactants that consists of dodecyl benzene sodium sulfonate with polyvinyl alcohol (DBSS/PVA) and DBBS with polyoxyethylene glycol monomethyl ether (DBBS/ POE). The obtained latices were characterized by 1 H NMR, rheological and morphological techniques. The effect of latices on the physicomechanical properties of ordinary Portland cement (OPC) pastes was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…On the other hand concrete has limited properties such as low ductility and crack resistance associated with hardening [2] , and adding waste tire to concrete could enhance the toughness. [3][4][5][6] Substantial research was carried out on the application of polymers in concrete [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . In many of the works waste tire rubber was added to the concrete as a substitute for fine or coarse aggregate [3][4][5][6][8][9][10][11][12][13][14][15][16][17][18][19] , while Ganjian et al [7] used waste tire powder as a replacement of cement.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand concrete has limited properties such as low ductility and crack resistance associated with hardening [2] , and adding waste tire to concrete could enhance the toughness. [3][4][5][6] Substantial research was carried out on the application of polymers in concrete [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . In many of the works waste tire rubber was added to the concrete as a substitute for fine or coarse aggregate [3][4][5][6][8][9][10][11][12][13][14][15][16][17][18][19] , while Ganjian et al [7] used waste tire powder as a replacement of cement.…”
Section: Introductionmentioning
confidence: 99%
“…Variation of four indexes manifests that the mix of WRA effectively improved the workability of fresh CGCBM for the mixing of WRA which contributes to increase the Advances in Materials Science and Engineering electrostatic repulsion between molecules, decrease surface tension of interface between solid and liquid, and decrease the wetting angle. In this test, the two WRAs are strong electrolytes with negative charges; if they were mixed, the lipophilic group will actively adhere to the surface of cement and fly ash particles, and the hydrophilic group will direct to water molecules [26][27][28][29][30]. is directional arrangement of WRA molecules makes the surface of cement and fly ash particles absorbed with like charge and form water film with a certain thickness which prevent forming flocculated structure.…”
Section: Slump and Slump Flowmentioning
confidence: 99%
“…Styrene/methacrylate copolymers play a key role in the family of polymers latex used in Portland cement [ 14 – 16 ]. Negim et al [ 17 ] showed that the rheological, physical, and mechanical properties of pastes are improved by using styrene/methacrylate polymer in the presence of different cosurfactants. These included DBSS/PVA and DBSS/POE.…”
Section: Introductionmentioning
confidence: 99%